PEMBERIAN Lactobacillus sp. PADA PAKAN UNTUK MENINGKATKAN PERTUMBUHAN UDANG VANAME (Litopenaeus vannamei) DI TAMBAK INTENSIF - juna, Junaidi; Witoko, Pindo; Indariyanti, Nur (Politeknik Negeri Lampung, 2022)
White shrimp (Litopenaeus vannamei) is one of the economically important shrimp that has several advantages including tolerance of water conditions, can grow quickly, and thick flesh. One of the problems in white shrimp cultivation is the slow growth of white shrimp due to inappropriate feed management. The addition of grampositive bacteria to the feed is scientifically believed to increase the growth of white shrimp. Among the grampositive bacteria that are commonly added to white shrimp aquaculture activities, namely Lactobacillus sp., this bacterium has many advantages for the survival of white shrimp in aquaculture activities. The addition of Lactobacillus sp. can increase the digestibility of feed due to simplification of complex proteins into simpler proteins so that the feed is easily absorbed by white shrimp. The results obtained from the administration of Lactobacillus sp. bacteria in the feed were getting very good growth results, the growth results from the lowest to the highest were A1 = 23.8 grams/head, A2=28.1 gram/head, A3=24.3 gram/head, A4=22.1 gram/head, A5=22.4 gram/head, A6=18.8 gram/head.